Silicon Nitride Interferometers for Optical Sensing with Multi-micron Dimensions. Issue 1 (1st December 2022) - Costa, João; Almeida, Daniel; Fantoni, Alessandro; Lourenço, Paulo; Vieira, Manuela
Abstract: Increasing the size of the smallest features of Photonic Integrated Circuits (PICs) to multi-micron dimensions can be advantageous to avoid expensive and complex lithographic steps in the fabrication process. In applications where extremely reduced chip size is not a requirement, the design of devices with multi-micron dimensions is potential interesting to avoid the need for e-beam lithography. Another benefit is that making the dimensions larger reduces the effect of lithographic imperfections such as waveguide surface roughness. However, the benefits do not come without limitations. Coupling the light in and out of the circuit is more challenging since diffraction gratings are not available when designing for such large dimensions. Circuit bends must have a larger radius of curvature and the existence of multimode propagation conditions can have detrimental impact in the performance of several devices, such as interferometers. In this study we perform simulations of the coupling between a lensed multimode optical fiber and a multi-micron a-SiN:H rib waveguide. Light coupling efficiency is analyzed as a function of distance variations using the FDTD method and compared with coupling to a strip waveguide. Moreover, we use numerical simulations to study the performance of a Mach-Zehnder interferometer sensitive to refractive index variations. Both the interferometer, splitters and combiners are designed with multi-micron dimensions.